Application of Theory of Planned Behavior in Prediction of Factors Affecting the Intention of Plagiarism - Leili Salehi; Masoumeh Ghasemzadeh (Zanjan University of Medical Sciences and Health Services, 2018)
Background & Objective: Plagiarism has been turned into a major concern for universities. The theory of planned behavior (TPB) is probably one of the most important predictive patterns for plagiarism in students. This cross-sectional study was performed to determine the use of TPB in the prediction of factors affecting plagiarism in 2016. Materials and Methods: In total, 200 MSc students at the stage of writing a dissertation were selected from Iran University of Medical Sciences, Tehran, Iran through convenience sampling. Age of students was 29.25±13.4 years. Moreover, 75.5% of the subjects were married, and 45.5% of the students were male. Data were collected using a self-administered questionnaire divided into three sections of demographic characteristics, planed behavior model constructs, and intent of plagiarism. In addition, data analysis was performed in SPSS version 19 using descriptive and analytical statistics (t-test, ANOVA, and multivariate regression). Results: A significant positive relationship was observed between positive attitude and intent of plagiarism. In other words, positive attitude significantly predicted the intent of plagiarism (P=0.007). On the other hand, a reverse and significant association was found between negative attitude and intent of plagiarism. Furthermore, there was a direct and significant correlation among subjective norms, perceived behavioral control, and intention. Conclusion: According to the results of this study, a direct and significant relationship exists between positive attitude toward and intent of plagiarism. In this regard, proper educational programs can be designed to correct this attitude.